FOOD AND FEEDING HABITS OF SILVER POMFRET PAMPUS ARGENTEUS (EUPHRASEN) FROM BAY OF BENGAL WITH A NOTE ON ITS SIGNIFIICANCE IN FISHERY - Pati, S (Indian Journal of Fisheries, 2011)
A detailed study of the food and feedbg habits of siil<ver pomf,ret, Pampus argenteus (Euplbrasen) was undertaken f.rom ,Bay of ’Bengal ’along the Oriss’a coast. Copepod formed the main item in the diet followed by maHer jeHy fiShes and Iphytoplankters. A vlIIriety of smaliler crustacea, ,polyC’haetes, fish e gs, -and fishlarvae occurred in minor quantities. The p0s4:-larvae feed, on phytoplankton and a variety of zoopla:Jktonic organisms are added to Â·the diet doci’1lg ubsequent growth. The fish unde,rtakes diurnal, ve,rtical migration ,in search of copepods, moving towards the surface after sunset and sinking tOo the bottom during Â·the day time